Bagaimana Pola Perencanaan dan Pengelolaan Keuangan Keluarga Muslim Etnis Arab Yang Berprofesi Ustadz dan Dokter di Surabaya - Syelvi Salama Binti Abdullah Bazher; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The purpose of this study was to determine how the pattern of financial planning and management of ethnic Arab families in Surabaya. This study used descriptive qualitative approach. The data collection is done by Interview and observation. The analysis technique used is the domain analysis techniques, taxonomy and componential.The results of this study there are some interesting phenomena to be discussed related to the pattern of financial planning and management arab ethnic family in Surabaya namely: managing income that the arab ethnic family uphold the principles to qowwam husband was sustained to shalihaan wife. Managing highly prioritize the settlement of this case is the most important prior to meeting the needs of the family. Managing dream has rules of jurisprudence life priorities, namely mukhodima ahamminal Muhin. Managing surplus and deficit has a principle to prioritize investment of the savings. managing contigencie social capital as a protection of the family.